Urbanization and its Effects on Environment and Socio-economic Sustainability; Evidence from Dire Dawa, Ethiopia - Dawud Chane Mekonnen; Habtamu Alebachew Legass (Sharia Oikonomia Law Journal, 2024)
The impact of urbanization on environmental sustainability is a critical issue that requires careful planning and management to ensure positive outcomes. This study aims to assess the effects of urbanization on urban environmental sustainability. A descriptive research design was employed to achieve this objective. Out of nine urban kebeles, five were purposively selected based on their relevance to the study. The sample size consisted of 394 respondents selected from a total target population of 29,932. Both primary and secondary sources of data were utilized, including questionnaires, interviews, observations, and document reviews. Data analysis involved the use of percentages, frequencies, diagrams, and charts. The findings revealed that rural-urban migration was a primary driver of urbanization, leading to rapid urban growth and associated challenges. Sustainable urban development initiatives were found to be inadequately implemented, resulting in the overconsumption of natural resources, improper waste disposal, and deforestation. While urbanization brought positive effects such as job opportunities and improved infrastructure access, negative consequences like informal settlements, crime, and high living costs were also evident. The study highlighted a lack of government focus on urban sustainability, emphasizing the need for increased agricultural development in rural areas to curb migration. Recommendations included stricter enforcement of laws, community training on environmental conservation, and the implementation of sustainable practices such as tree planting and waste recycling. Encouragingly, supporting underprivileged communities to improve their livelihoods was also advised to enhance overall urban sustainability.